2000
DOI: 10.1152/physrev.2000.80.1.83
|View full text |Cite
|
Sign up to set email alerts
|

Load-Regulating Mechanisms in Gait and Posture: Comparative Aspects

Abstract: How is load sensed by receptors, and how is this sensory information used to guide locomotion? Many insights in this domain have evolved from comparative studies since it has been realized that basic principles concerning load sensing and regulation can be found in a wide variety of animals, both vertebrate and invertebrate. Feedback about load is not only derived from specific load receptors but also from other types of receptors that previously were thought to have other functions. In the central nervous sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
334
0
4

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 480 publications
(351 citation statements)
references
References 486 publications
(535 reference statements)
13
334
0
4
Order By: Relevance
“…Normally, operation of the closed-loop postural mechanisms is based mainly on the somatosensory information coming from limb mechanoreceptors rather than on vestibular and visual inputs [2,6,12,32]. The corresponding limb afferents give rise to two postural reflex loops, spinal and spino-supraspinal [5,9,11,13,17].…”
Section: Activation Of Postural Mechanisms In Postmammillary Rabbitsmentioning
confidence: 99%
“…Normally, operation of the closed-loop postural mechanisms is based mainly on the somatosensory information coming from limb mechanoreceptors rather than on vestibular and visual inputs [2,6,12,32]. The corresponding limb afferents give rise to two postural reflex loops, spinal and spino-supraspinal [5,9,11,13,17].…”
Section: Activation Of Postural Mechanisms In Postmammillary Rabbitsmentioning
confidence: 99%
“…Ib afferents from GTOs have been shown to be responsible for increasing muscle activity in response to increased limb load in cats (Duysens and Pearson, 1980;Pearson, 1995;Pearson and Collins, 1993). Subsequently, Dietz et al (1992) and Duysens et al (2000) have argued that GTOs signal load in humans as well. In addition, cutaneous afferents from plantar mechanoreceptors in the foot have been shown to be important for postural control (Kavounoudias et al 2001) and compensatory postural reflexes elicited in response to a forward fall while standing (Do et al, 1990).…”
Section: Modulation Of Ankle Muscle Postural Reflex Magnitude Followimentioning
confidence: 99%
“…Reactive postural control entails a response, mediated by postural muscle reflexes, to a sudden unexpected perturbation applied to the body and relies on the central nervous system's (CNS) ability to interpret afferent information to ensure that the centre of mass (COM) stays within the base of support. Proprioceptive afferents from extensor muscles in the legs and exteroceptive afferents from mechanoreceptors in the foot are among the available inputs to the CNS to modulate standing or locomotor postural reflexes (Duysens et al, 2000). It has been suggested that these afferent inputs can provide information regarding load, and thus, have been referred to as load receptors and are particularly useful in signalling COM position (Dietz et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second one concerns more specifically the equilibrium system related to the body configuration and posture control. The third one is comprised of phasic feedback mechanisms activating, modulating, and further developing central pattern generators (CPGs) and other neural networks, using reflexive (neural; Duysens et al 2000) and preflexive (mechanical; Zehr and Stein 1999) factors.…”
Section: Mechanics Of Walkingmentioning
confidence: 99%